Sustainable Coffee Agroforestry Development in Rural Indonesia: Impacts on Community Income, Ecosystem Services, and Food Security in Buluh Mario Village, Sipirok District - Warsito, Kabul; Asmaq, Nur; Irawan, Indra; Hutabarat, Diki Wahyudi; Saputra, Dony; Manullang, Tawanli (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
This community service program implements an Arabica coffee agroforestry system in Buluh Mario Village through two main phases: (1) Participatory Rural Appraisal (PRA) survey to identify local potential and challenges, and (2) socialization and training based on Participatory Agricultural Extension Methodology (PAEM) covering Good Agricultural Practices (GAP), shade tree management, land conservation, and specialty coffee marketing. Results demonstrate high biophysical potential of Buluh Mario Village and very positive community response. Conclusion: the synergy between land suitability and community readiness establishes a strong foundation for sustainable coffee agroforestry development that improves farmer livelihoods while preserving ecosystem integrity.